2006
DOI: 10.1007/s00422-006-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct extraction of curvature-based metric shape from stereo by view-modulated receptive fields

Abstract: Any computation of metric surface structure from horizontal disparities depends on the viewing geometry, and analysing this dependence allows us to narrow down the choice of viable schemes. For example, all depth-based or slant-based schemes (i.e. nearly all existing models) are found to be unrealistically sensitive to natural errors in vergence. Curvature-based schemes avoid these problems and require only moderate, more robust view-dependent corrections to yield local object shape, without any depth coding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 56 publications
(132 reference statements)
2
11
0
Order By: Relevance
“…These results supported stereo-curvature adaptation at the percept level. In a more recent study (Noest, Van Ee, & Van Den Berg, 2006), a significant sCAE was found in the context of moving fixation along Lissajous paths, suggesting a dominant adaptation to shape curvature.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…These results supported stereo-curvature adaptation at the percept level. In a more recent study (Noest, Van Ee, & Van Den Berg, 2006), a significant sCAE was found in the context of moving fixation along Lissajous paths, suggesting a dominant adaptation to shape curvature.…”
Section: Introductionmentioning
confidence: 81%
“…The last type of adaptation stimuli were static curved surfaces with moving fixation, which was thought to be able to smear possible adaptation to disparity and its gradient. Observers in Noest et al (2006) inspected spherical or cylindrical adaptation stimuli consisting of a moderately sparse, semi-random array of wire-frame cubes centered on formal surfaces. The difference in aftereffect magnitude between static fixation and moving fixation along the Lissajous trajectory was used to examine whether adaptation to disparity or shape curvature occurred.…”
Section: Adaptation Levels Of Scaementioning
confidence: 99%
See 2 more Smart Citations
“…This differential approach can be extended in several ways; for example, it is possible to recover measures of surface shape, from the second-order structure of the disparity field [28,29,30]. These models are essentially local, and require that the disparity field is (or can be made) continuous.…”
Section: Relation To Previous Workmentioning
confidence: 99%